PENGARUH GENDER, PEMAHAMAN PERPAJAKAN DAN RELIGIUSITAS TERHADAP PERSEPSI PENGGELAPAN PAJAK - Lasmia Dharma; Restu Agusti; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to determine the influence of gender, tax knowledge, and religiusity to the perception of tax evasion. Independent variables used in this study are gender, tax knowledge, and religiusity, while the dependent variable in this study is the perception of tax evasion.Populations used in this study is quetionnaire, where the total population is used 125 students. The sampling technique used was purposive sampling technique in which the number of observations obtained this study was 45 (15x3). Data analysis conducted with multiple regression model with help of software SPSS version 20,0.Of the result of the testing that has been done, the partial regression test (t test) showed that the independent variables gender positive influence, tax knowledge negative influence,religiusity not influence. By variables gender, tax knowledge, and religiusity in this research can explain 48,2% the perception of tax evasion and the other 51,8% explain by other variable. Keywords: gender, tax knowledge, religiusity, and the perception of tax evasion